Developing the sports program according to the standards of total quality management - tamar, nadji; robi, Mohammed (sports creativity, 2025)
The composition of the university in Algeria moved from the system long term system in the short term in order to link the output configuration Ocean Economic and Social Council, in order to provide qualified eligible Petklfahoql, and the quality of quality, if we talked on the quality, it is not limited to the economic side, the concept of quality has become present in all fields , education, sociology, economy and quality in action sports and quality in the field of Sports Management, which oversees about the university in order to output trajectory athlete composed formation position to ensure optimum with the problems of sport and constraints that are present in the relevant institutions field sports with running a quality comprehensive customer satisfaction, or working in the sports field or the individual in society in general, in order to sport with the character of kinetic socio economic at the same time, we aim through this intervention indicate the nature of the composition of walking sports at the university from the perspective of mechanisms of planning and control, which include total quality in management sports that are talked about Joseph Juran in Onmozjh, as we are trying through this intervention illustrate this by drawing closer to being formed the student / learner to allocate administrative and management sports field